PENGARUH LATIHAN INTERVAL DAN MOTIVASI UNTUK MENINGKATKAN VO2MAX PADA ATLET FUTSAL - Iqbal Miftahudin; Muhamad Syamsul Taufik; Asep Ramdan Afriyuandi; Iwan Setiawan (Riyadhoh : Jurnal Pendidikan Olahraga, 2023)
This study aims to determine the effect of Interval Training and Motivation on increasing Vo2Max ability. The implementation of the research took place during the training process planned from June 2021 to August 2021. The research time was 2 months, the number of exercises was 18 meetings, with a frequency of 1 week 3 times. The research design used in this study is (pretest-posttest control group design). The results of this study have the effect of interval training and motivation on increasing Vo2max. The test results with the value of the interval training results 0.00 < 0.05 are declared significant, so interval training before and before being given treatment can be concluded that so from the results obtained that Interval Running Exercises have an effect on VO2max then the test results on training without exercise obtained 0.02 < 0.05, it is stated significant with exercise without exercise before being given treatment can guarantee that exercise without training methods has an effect on VO2max but it can be said that interval training has a more significant effect on increasing VO2max for athletes futsal.